Identification of the best practical education evaluation management based on virtual applications in the digital era - Nurmala, Nurmala; Irwan, Dede (International research journal of management, IT and social sciences, 2022)
This article identifies practical education evaluation governance by utilizing virtual applications when education is run in the digital era. The authors observed the learning phenomenon during the pandemic that, along with the government's policy of closing schools and reopening online classes, learning and evaluation also took place remotely. To discuss the results of practical investigations of educational evaluation governance by relying on virtual applications, we have obtained various supporting information that we found electronically on many educational evaluation literature sources relying on virtual applications from various publication sources in the form of books, magazines, newspapers and also scientific publications, namely the results of studies field recently. Based on the results of identification and discussion, we can summarize that evaluation is divided into formative and summative. We have found practical things in online learning evaluations, including online drag and drop activities, dialogue simulations, and online surveys. We hope that the results of this evaluation can add to the scientific treasures and efficient evaluations during the online learning period.